2018
DOI: 10.1002/ehf2.12347
|View full text |Cite
|
Sign up to set email alerts
|

Gender differences in Egyptian patients hospitalized with heart failure: insights from the European Society of Cardiology Heart Failure Long‐Term Registry

Abstract: Men and women with AHF differ significantly in baseline clinical characteristics and management but not in adverse outcomes. These findings emphasize the importance of individualized management and need for more comprehensive recruitment of women in clinical trials.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
18
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 17 publications
(20 citation statements)
references
References 35 publications
2
18
0
Order By: Relevance
“…Our study indicated one counterintuitive result that women bore a higher overall incidence of CHF than men did. However, previous investigations of sex-specific epidemiology of CHF have demonstrated that women with atrial fibrillation have a higher incidence of heart failure with preserved ejection fraction, especially in very old age compared with men 44–46. In this study, CVF was associated with an increased risk of CHF, and the results remained statistically significant across various age and sex strata, as well as with or without comorbidities.…”
Section: Discussionsupporting
confidence: 49%
“…Our study indicated one counterintuitive result that women bore a higher overall incidence of CHF than men did. However, previous investigations of sex-specific epidemiology of CHF have demonstrated that women with atrial fibrillation have a higher incidence of heart failure with preserved ejection fraction, especially in very old age compared with men 44–46. In this study, CVF was associated with an increased risk of CHF, and the results remained statistically significant across various age and sex strata, as well as with or without comorbidities.…”
Section: Discussionsupporting
confidence: 49%
“…Anemia was highly prevalent across regions, especially in Upper Egypt where it was seen in almost 80% of patients. Hassanein et al have reported that anemia is particularly prevalent among Egyptian women with HF as compared to men, 35.4% versus 18.9%, respectively [4]. In a systematic review and meta-analysis by Groenveld et al [10], anemia was associated with an increased risk of mortality in both systolic and diastolic HF.…”
Section: Discussionmentioning
confidence: 98%
“…The European Society of Cardiology Heart Failure Long-Term (ESC-HF-LT) Registry, in which Egypt participated as a member country, provided the first representative data on HF patients in the country [3]. Studies comparing the cohort of heart failure (HF) patients in Egypt to the European cohorts, as well as gender differences of HF patients within Egypt, have been published [4,5]. However, no study to date has compared the characteristics and outcomes of HF patients across the different regions of Egypt.…”
Section: Introductionmentioning
confidence: 99%
“…These studies could provide better understanding of the effect of the antidiabetes drugs on HF in patients with or without T2DM, and could potentiate to broaden the use of these drugs beyond their conventional therapeutic use. Moreover, many co-morbidities other than T2DM and prediabetes such as cachexia and muscle wasting, anaemia and iron deficiency, chronic obstructive pulmonary disease and sleep apnoea are also important in managing HF patients [44][45][46][47][48][49][50].…”
Section: Cardiovascular Outcomes With Sglt-2 Inhibitorsmentioning
confidence: 99%